Adaptation of the SAGEFS scale on attitudes toward gender equality in football in the international school context - Méndez-Hinojosa, Luz Marina; Gil-Madrona, Pedro; Zamorano-García, David; Simón-Piqueras, Juan Ángel; Padierna-Cardona, Juan Carlos; Flores-Ferro, Elizabeth; González-Villalobos, Martín Francisco; Pavlovic, Ratko; Maureira-Cid, Fernando; Gómez-Santos, Natalia; Morales-Calvo, Sonia; Cárdenas-Rodríguez, Magaly (Frontiers in Psychology, 2024)
The objective of the present study is to evaluate the psychometric properties of the Scale of Attitudes towards Gender Equality in Football in the Context of Schools (SAGEFS) in the international context. This sample was formed by N = 6,101 students. The study was conducted by applying the SAGEFS. The model of the three factors correlated in the complete simple and for each country was correlated using AFC. The structural model was appraised by employing eight indices: the relative Chi-squared index; the goodness of fit index and its adjusted formula; the normal fit index; the comparative fit index; the standardized Quadratic Mean and the Quadratic Mean Error of Approximation.To conclude, the results evidence the presence of psychometric properties that are indispensable for the measurement of attitudes toward gender equality in the contexts of schools..124 ** (.095, .